Core Conceptual Features of Successful Blended Learning in Higher Education: Policy Implications - Bekele, T.A.; Amponsah, S.; Karkouti, I.M. (Education Policy Analysis Archives, 2022)
COVID-19 has “taught” universities worldwide that using digital technologies to support Pure online or blended learning is a survival strategy. This lesson, plus the inclusion of technology in continental, national, and university policies and strategic plans implicate significant technology integration, especially blended learning, in higher education in the post-pandemic era. However, there is a lack of sound theoretical frameworks to adequately explain success indicators and success factors in blended learning. Existing frameworks provided particulars about the impacts of blended learning within certain contexts; none provided a comprehensive analysis of the significant factors thattranscend specific application contexts. Moreover, the frameworks did not offer clear conceptions of knowledge, teaching, learning, and technology and its role in learning. To better inform successful blended learning adoption, this study problematizes success indicators and success factors based on a configurative review of existing frameworks and emerging theoretical perspectives in higher education. A holistic conceptual framework that transcends context specificity is proposed to better inform policy making, instructional design, and teaching and learning. Conceptions of adaptive policy: policy as learning design and policy as practice are found relevant for blended learning policy making and analysis in higher education.
Research Article
Keywords: blended learning; higher education; policy making